PENGARUH LINGKUNGAN KERJA FISIK, KEPUASAAN KERJA DAN HUMAN RELATION TERHADAP KINERJA KARYAWAN PADAPT CITRA PUTERA UTAMA PRINGSEWU - Syarifuddin Syarifuddin; Winna Rahmawati (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to examine how employee performance at PT Citra Putera Utama Pringsewu is impacted by the physical work environment, job satisfaction, and interpersonal relationships. The study was carried out at PT Citra Putera Utama Pringsewu, where a decline in employee performance had an effect on business performance. The Partial Least square Structural Equation Model (PLS-SEM 3.0) is the analysis method used in the quantitative research method. With a total of 70 respondents, 20 women and 50 men. This sampling method uses non-probability sampling and saturated sampling techniques. “The analysis's findings indicate a significant positive relationship between the physical workspace, employee satisfaction, and interpersonal relationships and performance. Employee performance is influenced by the physical work environment, which also has an impac to job satisfaction, human relation, and employee performance. Employee performance at PT Citra Putera Utama Pringsewu is indirectly impacted by the physical work place.